GE_GERICHTE P/19096/2019 vom 25. Juni 2024 - GE Cour de justice (2024)
APPRÉCIATION DES PREUVES;ASSASSINAT;BRIGANDAGE;CRUAUTÉ;CONTRAINTE(DROIT PÉNAL);PAIX DES MORTS;INSTIGATION;INTERNEMENT(DROIT PÉNAL) | CP.112; CP.140; CP.262; CP.181; CPP.10; CP.140.ch4; CPP.343; CP.24; CP.64.al1